Mechanical and electrical properties of low density polyethylene filled with carbon nanotubes - Sabet, M. (2014)
Carbon nanotubes (CNTs) reveal outstanding electrical and mechanical properties in addition to nanometer scale diameter and high aspect ratio, consequently, making it an ideal reinforcing agent for high strength polymer composites. Low density polyethylene (LDPE)/CNT composites were prepared via melt compounding. Mechanical and electrical properties of (LDPE)/CNT composites with different CNT contents were studied in this research.